Interdisciplinary Teamwork and the Power of a Quality Improvement Collaborative in Tertiary Neonatal Intensive Care Units. Issue 2 (April 2015) - Grover, Theresa R.; Pallotto, Eugenia K.; Brozanski, Beverly; Piazza, Anthony J.; Chuo, John; Moran, Susan; McClead, Richard; Mingrone, Teresa; Morelli, Lorna; Smith, Joan R.
<x xml:space="preserve">Abstract</x> Significant gaps in healthcare quality and outcomes can be reduced via quality improvement collaboratives (QICs), which improve care by leveraging data and experience from multiple organizations. The Children's Hospital Neonatal Consortium Collaborative Initiatives for Quality Improvement team developed an infrastructure for neonatal QICs. We describe the structure and components of an effective multi-institutional neonatal QIC that implemented the "SLUG Bug" project designed to reduce central line-associated bloodstream infections (CLABSIs). The operational infrastructure of SLUG Bug involved 17 tertiary care neonatal intensive care units with a goal to reduce CLABSI in high-risk neonates. Clinical Practice Recommendations were produced, and the Institute of Healthcare Improvement Breakthrough Series provided the framework for the collaborative. Process measures studied the effectiveness of the collaborative structure. CLABSI rates decreased by 20% during a 12-month study period. Compliance bundle reporting exceeded 80%. A QIC score of 2.5 or more ("improvement") was achieved by 94% of centers and a score 4 or more ("significant improvement") was achieved by 35%. Frequent interactive project meetings, well-defined project metrics, continual shared learning opportunities, and individual team coaching were key QIC success components. Through a coordinated approach and committed leadership, QICs can effectively implement change and improve the care of neonates with complex diagnoses and rare diseases.